Stabilizing Inactive Conformations of MALT1 as an Effective Approach to Inhibit Its Protease Activity. Issue 9 (17th June 2020) - Hughes, Nicola; Erbel, Paul; Bornancin, Frédéric; Wiesmann, Christian; Schiering, Nikolaus; Villard, Frédéric; Decock, Arnaud; Rubi, Bertran; Melkko, Samu; Spanka, Carsten; Buschmann, Nicole; Pissot‐Soldermann, Carole; et al.
Abstract: The paracaspase MALT1 (mucosa associated lymphoid tissue lymphoma translocated gene 1) plays an important role in various immune pathways and is proposed as a therapeutic target for autoimmune disorders as well as different types of cancer, such as diffuse large B‐cell lymphoma (DLBCL). Different mechanisms are explored to inhibit the protease activity of MALT1 and two unrelated chemical scaffolds are discovered. Biophysical and structural studies reveal that both scaffolds stabilize the protease in an inactive conformation. While one ligand binds to the allosteric site at the interface between the caspase and the Ig3 domain, the other ligand binds to the active site using a so far undescribed mechanism. Iterative structure‐based drug discovery on one scaffold results in the identification of a potent, selective, and orally bioavailable MALT1 inhibitor. Abstract : The paracaspase MALT1 (mucosa associated lymphoid tissue lymphoma translocated gene 1) plays an important role in various immune pathways and is proposed as a versatile therapeutic target. Two unrelated chemical scaffolds binding to different sites and stabilizing the protease in an inactive conformation are discovered. One scaffold is optimized to MLT‐208, a potent and selective MALT1 inhibitor.